2009
DOI: 10.1073/pnas.0708837106
|View full text |Cite
|
Sign up to set email alerts
|

The keratin-related Ouroboros proteins function as immune antigens mediating tail regression in Xenopus metamorphosis

Abstract: Tail resorption during amphibian metamorphosis has been thought to be controlled mainly by a cell-autonomous mechanism of programmed cell death triggered by thyroid hormone. However, we have proposed a role for the immune response in metamorphosis, based on the finding that syngeneic grafts of tadpole tail skin into adult Xenopus animals are rejected by T cells. To test this, we identified two tail antigen genes called ouro1 and ouro2 that encode keratin-related proteins. Recombinant Ouro1 and Ouro2 proteins g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 26 publications
1
36
1
Order By: Relevance
“…Mack et al proposed that bile duct infection or injury due to rotavirus infection could be inciting factors leading to progressive, autoimmune-mediated damage of the biliary tree after recovery from infection (Mack & Sokol, 2005;Barnes et al, 2009). Incidentally, it has been revealed that programmed cell death in amphibian metamorphosis is induced by a selective auto-immune response, and that the immune system may contribute to the remodeling processes in vertebrate morphogenesis, universally (Mukaigasa et al, 2009). The onset of human BA always occurs during the pre-natal or perinatal periods despite the fact that rotavirus infection with acholic stool and other viral infections are so common among preschool children and infants under one year of age.…”
Section: Discussionmentioning
confidence: 99%
“…Mack et al proposed that bile duct infection or injury due to rotavirus infection could be inciting factors leading to progressive, autoimmune-mediated damage of the biliary tree after recovery from infection (Mack & Sokol, 2005;Barnes et al, 2009). Incidentally, it has been revealed that programmed cell death in amphibian metamorphosis is induced by a selective auto-immune response, and that the immune system may contribute to the remodeling processes in vertebrate morphogenesis, universally (Mukaigasa et al, 2009). The onset of human BA always occurs during the pre-natal or perinatal periods despite the fact that rotavirus infection with acholic stool and other viral infections are so common among preschool children and infants under one year of age.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the immune system in tail physiology becomes even more complex at pre-metamorphic and metamorphic stages when the tail is resorbed. Although tail degeneration is usually thought to be controlled mainly by a cell-autonomous mechanism of programmed cell death triggered by thyroid hormone, a critical involvement of the immune system has been shown [29]. Two keratin proteins, Ouro1 and Ouro2 proteins, specifically expressed in the tail skin, are necessary and sufficient to promote T cell-mediated tail regression.…”
Section: Existing Potential Of the Xenopus Model For Comparative Imentioning
confidence: 99%
“…These results strongly suggest that the tadpole immune system recognizes tail-skin-specific Ouro1/2 proteins as larval antigens during the metamorphosis climax, and the recognition is pivotal to tail resorption. This immunological rejection model suggests that newly differentiated adult-type immune cells recognize Ouro proteins as non-self targets for tail dissolution, allowing the elimination of larval cells during metamorphosis (35).…”
Section: Immunological Rejection Through Recognition Of Epidermal Ourmentioning
confidence: 99%